SOCIAL INTERACTION SPACES IN KAMPUNG PASIR GINTUNG, BANDAR LAMPUNG, INDONESIA - Tamariska, Stirena Rossy; Fatna, Agestha Bio Moze (Jurnal Ilmiah Arsitektur, 2025)
The rapid growth of settlements in Indonesian metropolitan areas compels migrants to establish territories spontaneously, resulting in increasingly dense communities and the need for deliberate social spaces. These spaces emerge organically among residents who share long-term living experiences, cultural backgrounds, and daily activities. This study explores the characteristics of communal spaces in urban kampungs using a qualitative narrative method. Data were collected by observing the Sukamampir road corridor in Pasar Gintung, Bandar Lampung, Indonesia. The findings show that residents have transformed the road corridor into meaningful spaces for interaction, focusing on gathering activities at specific points. Given the limited spatial resources in the kampung, the study examines how citizens adaptively create places for social interaction within the remaining available areas. Activities such as sitting, standing, playing, eating, and buying and selling food occur within the corridor, facilitating daily interactions. This research highlights the adaptive strategies employed by residents to sustain social engagement amidst spatial constraints.